PERAN MANAJEMEN STRES BERBASIS MINDFULLNES DAN INTELEGENCIA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BEDROCKHOTEL KUTA - I Gusti Ngurah Satya Darma Widana; Ni Luh Kardini; Ni Putu Yuli Tresna Dewi; Lale Ajeng Khalifatun Wardani (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to evaluate the role of mindfulness-based stress management and intelligence on employee productivity at the Bedrock Hotel Kuta. This study used primary data obtained through a questionnaire, and 67 employees were selected using a saturated sampling method. Multiple regression analysis was used to test the research hypotheses. The results showed that mindfulness had a significant positive effect on productivity, and intelligence also had a positive effect on productivity. Furthermore, stress management had a significant positive effect on productivity. Simultaneous test results indicated that mindfulness, intelligence, and stress management collectively had a significant positive effect on productivity. The coefficient of determination indicated that mindfulness, intelligence, and stress management in the regression model explained 51% of the variation in productivity, with the remainder influenced by other independent variables.